Solve for x (complex solution)
x\in \frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}}{6},\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}e^{\frac{4\pi i}{3}}}{6},\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}e^{\frac{2\pi i}{3}}}{6},-1,\frac{-\sqrt{3}i+1}{2},\frac{1+\sqrt{3}i}{2}
Solve for x
x=-1
x=\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}}{6}\approx 0.941036029
Graph
Share
Copied to clipboard
6t^{2}+t-5=0
Substitute t for x^{3}.
t=\frac{-1±\sqrt{1^{2}-4\times 6\left(-5\right)}}{2\times 6}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 6 for a, 1 for b, and -5 for c in the quadratic formula.
t=\frac{-1±11}{12}
Do the calculations.
t=\frac{5}{6} t=-1
Solve the equation t=\frac{-1±11}{12} when ± is plus and when ± is minus.
x=-\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}e^{\frac{\pi i}{3}}}{6} x=\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}ie^{\frac{\pi i}{6}}}{6} x=\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}}{6} x=-1 x=\frac{1+\sqrt{3}i}{2} x=\frac{-\sqrt{3}i+1}{2}
Since x=t^{3}, the solutions are obtained by solving the equation for each t.
6t^{2}+t-5=0
Substitute t for x^{3}.
t=\frac{-1±\sqrt{1^{2}-4\times 6\left(-5\right)}}{2\times 6}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 6 for a, 1 for b, and -5 for c in the quadratic formula.
t=\frac{-1±11}{12}
Do the calculations.
t=\frac{5}{6} t=-1
Solve the equation t=\frac{-1±11}{12} when ± is plus and when ± is minus.
x=\frac{\sqrt[3]{5}\times 6^{\frac{2}{3}}}{6} x=-1
Since x=t^{3}, the solutions are obtained by evaluating x=\sqrt[3]{t} for each t.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}